Amyloid β directly interacts with NLRP3 to initiate inflammasome activation: identification of an intrinsic NLRP3 ligand in a cell-free system - Ayaka Nakanishi; Naoe Kaneko; Hiroyuki Takeda; Tatsuya Sawasaki; Shinnosuke Morikawa; Wei Zhou; Mie Kurata; Toshihiro Yamamoto; Sheikh Mohammad Fazle Akbar; Tamotsu Zako; Junya Masumoto (BMC, 2018)
Abstract Background Alzheimer's disease is a neurodegenerative disease characterized by the interstitial deposition of amyloid β (Aβ) plaque, which is thought to be related to chronic neuroinflammation. Aβ is known to make fibrils via oligomers from monomers. Aβ has been reported to activate the NLRP3 inflammasome in infiltrated macrophages. NLRP3, an intracellular pattern recognition receptor, has been reported to recognize numerous pathogens and/or metabolites and form complexes with adopter protein ASC to make the inflammasome, an interleukin (IL)-1β-processing platform. Although reactive oxygen species from mitochondria have been reported to be involved in the activation of the NLRP3 inflammasome in microglial cells upon the deposition of Aβ, whether Aβ directly or indirectly activates the NLRP3 inflammasome remains unclear. Methods We prepared monomers, oligomers, and fibrils of Aβ, which promoted the interaction between NLRP3 and each form of Aβ and analyzed the interaction between NLRP3 and ASC induced by each form of Aβ in a cell-free system with the amplified luminescent proximity homogeneous assay. We also confirmed the physiological relevance in a cell-based assay using human embryonic kidney 293T cells and human peripheral mononuclear cells. Results Monomers, oligomers, and fibrils of Aβ were successfully prepared. Aβ oligomers and fibrils interacted with NLRP3. Aβ oligomers and fibrils induced the interaction between NLRP3 and ASC. However, Aβ monomers did not interact with NLRP3 or induce interaction between NLRP3 and ASC in the cell-free system, and IL-1β was not secreted according to the cell-based assay. Conclusion Oligomerized Aβ originating from non-toxic Aβ monomers directly interacted with NLRP3, leading to the activation of the NLRP3 inflammasome. This may be an attractive target for the treatment of Alzheimer's disease.